2020
DOI: 10.1097/coc.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia, BMI, and Inflammatory Biomarkers on Survival in Advanced Hepatocellular Carcinoma Treated With Anti-PD-1 Antibody

Abstract: Background: Sarcopenia and inflammation are independently associated with worse survival in cancer patients. This study aims to determine the impact of sarcopenia, body mass index (BMI), and inflammatory biomarkers on survival in advanced hepatocellular carcinoma (HCC) patients treated with anti-PD-1 antibody-based immunotherapy. Methods: A retrospective review of advanced HCC patients treated with immunotherapy at Winship Cancer Institute between 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 63 publications
2
59
2
Order By: Relevance
“… 27 However, the practicability of the model is insufficient in clinical practice. For HCC, the NLR and PLR were reported to have strong predictive roles in anti-PD-1 therapy, 20 , 28 , 29 which was verified in our study. With the combination of albumin and lymphocytes, our study suggested that the presence of the systemic inflammatory response revealed by PNI was the optimal tool in the assessment of survival in HCC patients treated with PD-1 inhibitors compared with the other inflammation-based scores.…”
Section: Discussionsupporting
confidence: 83%
“… 27 However, the practicability of the model is insufficient in clinical practice. For HCC, the NLR and PLR were reported to have strong predictive roles in anti-PD-1 therapy, 20 , 28 , 29 which was verified in our study. With the combination of albumin and lymphocytes, our study suggested that the presence of the systemic inflammatory response revealed by PNI was the optimal tool in the assessment of survival in HCC patients treated with PD-1 inhibitors compared with the other inflammation-based scores.…”
Section: Discussionsupporting
confidence: 83%
“…In previous study, peripheral blood parameters can reflect the system state of human bodies [ 15 17 ]. NLR and other hematologic parameters have become biomarkers to predict the overall survival (OS) and anti-PD-1 / PD-L1 treatment effect of diverse types of cancer [ 18 , 19 ]. PLR, MLR and SII were also reported to be potential biomarkers for predicting OS and the response to anti-PD-1/PD-L1 antibody treatment in different types of cancer [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study of 976 patients, 65% of whom treated for NSCLC, a median OS of 26.6 months (95% CI: 21.4–36.8) was reported, and median OS was higher in patients with a BMI ≥ 25 (HR= 0.33 95% CI: 0.28–0.41) [ 13 ]. Most of the other studies demonstrating a relationship between BMI and outcome on immunotherapy [ 17 , 20 , 21 , 22 , 23 ] were also performed on patients with NSCLC [ 16 , 24 , 25 ], renal carcinoma, or melanoma [ 12 , 26 , 27 ]. Moreover, two studies, including patients treated by immunotherapy or chemotherapy, demonstrated a prognostic effect of BMI exclusively in patients on immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate Cox regression models were generated by a backward approach after testing in univariate models to estimate patient survival in association with BMI adjusted for covariates, including toxicity, performance status during first-line immunotherapy (0 to 4), and MSI. A landmark analysis was then performed to deal with the survivor bias resulting from patients responding to immunotherapy being exposed to immunotherapy for longer, and therefore being more likely to develop irAEs than non-responder patients, in whom immunotherapy was stopped earlier [ 20 ]. These analyses considered only toxicities occurring in the first three months of immunotherapy for the classification of groups, with the exclusion of patients who died or were censured before three months of treatment.…”
Section: Methodsmentioning
confidence: 99%